Early Childhood Bilingualism Leads to Advances in Executive Attention: Dissociating Culture and Language - YANG, Sujin (Institutional Knowledge at Singapore Management University, 2011)
This study investigated whether early especially efficient utilization of executive functioning in young bilinguals would transcend potential cultural benefits. To dissociate potential cultural effects from bilingualism, four-year-old U.S. Korean-English bilingual children were compared to three monolingual groups – English and Korean monolinguals in the U.S.A. and another Korean monolingual group, in Korea. Overall, bilinguals were most accurate and fastest among all groups. The bilingual advantage was stronger than that of culture in the speed of attention processing, inverse processing efficiency independent of possible speed-accuracy trade-offs, and the network of executive control for conflict resolution. A culture advantage favoring Korean monolinguals from Korea was found in accuracy but at the cost of longer response times.